2011
DOI: 10.1002/jcp.22421
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase D1 promotes anchorage‐independent growth, invasion, and angiogenesis by human pancreatic cancer cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal diseases. Novel molecularly targeted therapies are urgently needed. Here, we extended our studies on the role of protein kinase D1 (PKD1) in PDAC cell lines. Given that Panc-1 express moderate levels of PKD1, we used retroviral-mediated gene transfer to create a Panc-1 derivative that stably over-expresses PKD1 (Panc-1-PKD1). Reciprocally, we used shRNA targeting PKD1 in Panc-28 to produce a PKD1 under-expressing Panc-28 derivative (Panc-28-shPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 47 publications
3
57
0
Order By: Relevance
“…Consistent with the results presented here, PKD1 has been also implicated in the motility of fibroblasts (34,61), endothelial cells (11), and prostate cancer cells (22,63) and invasion of pancreatic cancer cells (30). However, other studies concluded that PKD1 inhibits the motility of other cell lines, including HeLa and breast cancer cell lines (10,32).…”
Section: G363 Pkd1 Promotes Migration Of Intestinal Epithelial Cellssupporting
confidence: 90%
“…Consistent with the results presented here, PKD1 has been also implicated in the motility of fibroblasts (34,61), endothelial cells (11), and prostate cancer cells (22,63) and invasion of pancreatic cancer cells (30). However, other studies concluded that PKD1 inhibits the motility of other cell lines, including HeLa and breast cancer cell lines (10,32).…”
Section: G363 Pkd1 Promotes Migration Of Intestinal Epithelial Cellssupporting
confidence: 90%
“…New recurrent PRKD1 gene rearrangements and variant fusions have been found in cribriform adenocarcinoma of the oropharynx (71). PKD1 has been proposed as a therapeutic target in pancreatic (15,31,37) and colon (69) cancers, although a different conclusion has also been presented (57). It is conceivable that the PKD/␤-catenin cross talk identified here contributes to the mechanism(s) by which PKDs promote malignant transformation of epithelial cells, but further systematic studies are needed to prove this hypothesis.…”
Section: Discussionmentioning
confidence: 78%
“…However, specific and detailed functions for distinct PKD isoforms have not been addressed so far. In a previous work, Ochi et al (38) have proposed a function for PKD1 in the regulation of anchorage-dependent growth. However, the properties of distinct PKD isoforms were not directly compared or addressed by inhibitors that are not isoform-specific.…”
Section: Discussionmentioning
confidence: 99%